2012
DOI: 10.1111/j.1600-0714.2012.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor, CYP27B1 and CYP24A1 genes polymorphisms association with oral cancer risk and survival

Abstract: Our findings indicate that CYP24A1 gene polymorphism might have an influence on the susceptibility to oral cancer. VDR FokI polymorphism was associated with worse survival and could be considered as an independent prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 37 publications
7
41
0
Order By: Relevance
“…The results of crude and adjusted odds ratio analysis showed that FokI heterozygous and mutated genotypes are associated with increased OLP risk compared with the wild type form. Recent findings reported absence of an association but worse survival in wt carriers in oral cancer patients from the Serbian population [21]. VDR FokI polymorphism is intensively studied in various types of diseases, mainly cancers, thus findings among studies are inconsistent, probably as a result of different investigated pathologies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of crude and adjusted odds ratio analysis showed that FokI heterozygous and mutated genotypes are associated with increased OLP risk compared with the wild type form. Recent findings reported absence of an association but worse survival in wt carriers in oral cancer patients from the Serbian population [21]. VDR FokI polymorphism is intensively studied in various types of diseases, mainly cancers, thus findings among studies are inconsistent, probably as a result of different investigated pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…Identified polymorphisms in vitamin D related genes were extensively studied in relation to various types of diseases, such as cancer [14][15][16], autoimmune [17,18], and inflammatory diseases [19,20]. Our research group previously reported association between VDR and CYP24A1 gene polymorphisms with oral cancer risk and survival [21], while polymorphisms in these genes have not previously been investigated in OLP patients.…”
Section: Introductionmentioning
confidence: 98%
“…Studies by Zeljic et al (2012) of a cohort of 110 patients with OSCC and 122 healthy controls demonstrated that the presence of VDR and CYP24A1 gene polymorphisms affected oral cancer risk and survival. CYP24A1 gene polymorphism (rs2296241) was found to increase susceptibility to oral cancer, while the wild type ff genotype of FokI polymorphism was associated with lower survival rates.…”
Section: Oral Cancermentioning
confidence: 99%
“…Upon ligand binding, VDR heterodimerize with RXR or RAR, and regulate the transcription of more than a hundred genes, involved not only in calcium and phosphate homeostasis but also in cell proliferation, differentiation, and apoptosis (Chung et al 2009). Accumulating results revealed the association between vitamin D deficiency and vitamin D-related genes with different cancer types, including breast, prostate, colorectal, oral, lung cancer, melanoma and acute myeloid leukemia (Feldman et al 2014;Davis and Milner 2011;Zeljic et al 2012, Puccetti et al 2002. In addition, the gene expression of VDR and CYP24A1 gene, coding for 24-hydroxylase, enzyme involved in the vitamin D catabolism, and CYP27B1, coding for 1α-hydroxylase, involved in anabolism, is mediated by epigenetic modifications (Hobaus et al 2013;Fetahu et al 2014).…”
Section: Essential Micronutrientsmentioning
confidence: 98%